PENERAPAN METODE AHP DALAM PENENTUAN KRITERIA SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENJUAL PADA KANTIN - Fandli Supandi; Kusrini Kusrini; Hanif Al Fatta (Universitas Janabadra, 2019)
Canteen is one of the most important places to be owned by a particular institution including educational institutions such as universities, in the canteen itself there are sellers - sellers who are the main factors that determine the consumer's decision to the canteen. in this study we will discuss how to determine the priority weights of criteria to be used as an evaluation parameter for the selection of prospective sellers who will be accepted in a canteen. The method used is the Analytical Hierarchy Process (AHP), the stages in the AHP method begin with the process of defining the problem, making a hierarchical structure that begins with general objectives, followed by criteria and alternative choices, Creating pairwise comparison matrices, normalizing data, calculating values eigen vector and test its consistency, calculate eigen vector from each paired comparison matrix, test the consistency of hierarchy. If it does not meet with CR <0.01, the pairwise comparison process must be carried out again. The results of this study are a priority weight of each criterion that will be used for the selection process of prospective sellers in the canteen.Keywords: Canteen, AHP, criter